2013
DOI: 10.1037/a0027809
|View full text |Cite
|
Sign up to set email alerts
|

Voices of older Asian Indian immigrants: Mental health implications.

Abstract: Recent research indicates a risk of isolation and psychological distress and underutilization of mental health services among older immigrants (Hernandez & Bigatti, 2010;Mui & Kang, 2006). The present study examined the perspectives of Asian Indian older adults and aimed to bridge gaps in understanding aging in the immigrant context. Semistructured interviews with 18 Asian Indian older adults (8 men and 10 women) were analyzed using content analysis. Four broad categories emerged from the data including: (a) c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
24
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(28 citation statements)
references
References 34 publications
3
24
0
Order By: Relevance
“…Such results are consistent with evidence from a qualitative study with older Indian immigrants recruited from an Indian seniors' community programme (Tummala-Narra et al, 2013). Their stories revealed that participation in socially embedded, co-ethnic networks helped them cope with cultural changes, isolation, and loneliness (Tummala-Narra et al, 2013).…”
supporting
confidence: 79%
See 2 more Smart Citations
“…Such results are consistent with evidence from a qualitative study with older Indian immigrants recruited from an Indian seniors' community programme (Tummala-Narra et al, 2013). Their stories revealed that participation in socially embedded, co-ethnic networks helped them cope with cultural changes, isolation, and loneliness (Tummala-Narra et al, 2013).…”
supporting
confidence: 79%
“…Their stories revealed that participation in socially embedded, co-ethnic networks helped them cope with cultural changes, isolation, and loneliness (Tummala-Narra et al, 2013). In accord, older transnational immigrants, either on extended family visits or permanently resettled in California, were lonelier and more dissatisfied when isolated from engaging socially beyond their kin networks (Treas & Mazumdar, 2002).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Even though family issues and the sociocultural expectations of the AI community were stressors, they were also often seen as a source of support, strength, acceptance, and protection. In line with other studies, AI women may be more inclined to utilize informal support mechanisms such as these, rather seeking mental health care [ 7 , 47 ]. Acculturation balanced with maintaining AI traditions was expressed as evidence of resilience and ultimate achievement, which results in wellbeing and satisfaction with life.…”
Section: Discussionsupporting
confidence: 81%
“…12,4752 Predictors of depression among SA older adults include abuse and neglect, social isolation, and acculturative stress. 12 In one study, poorer physical health and a more traditional ethnic identity were correlated with depressive symptoms in a group of older SAs in the U.S. 50 These factors persisted in both limited English proficient and English proficient study groups.…”
Section: Resultsmentioning
confidence: 99%